2020
DOI: 10.1007/s10530-020-02351-0
|View full text |Cite
|
Sign up to set email alerts
|

Control of invasive ring-necked parakeet (Psittacula krameri) in an island Biosphere Reserve (La Palma, Canary Islands): combining methods and social engagement

Abstract: The ring-necked parakeet (Psittacula krameri) has been naturalised in La Palma Island Biosphere Reserve since the late 1990s. Due to landowners' complaints about the impact of parakeets on crops, a control scheme was implemented to eliminate the known population, initially estimated at 70 birds. The programme finally comprised three different phases. Between December 2015 and September 2016, 107 parakeets were removed by trapping using 14 decoy traps. Due to inefficient handling and trap shyness developed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…However, it could be that our data are conservative regarding the real costs incurred in protected areas. For example, Saavedra and Medina (2020) showed that an eradication programme implemented in La Palma Island, Spain, prevented the expansion of the ring-necked parakeet (Psittacula krameri) into La Palma Island Biosphere. These costs were, however, recorded at the island level, not only in the protected lands.…”
Section: Regional Management and The Need For Effective National Coordination Of Actionsmentioning
confidence: 99%
“…However, it could be that our data are conservative regarding the real costs incurred in protected areas. For example, Saavedra and Medina (2020) showed that an eradication programme implemented in La Palma Island, Spain, prevented the expansion of the ring-necked parakeet (Psittacula krameri) into La Palma Island Biosphere. These costs were, however, recorded at the island level, not only in the protected lands.…”
Section: Regional Management and The Need For Effective National Coordination Of Actionsmentioning
confidence: 99%
“…Amongst conservation scientists, global consensus highlights that alien species represent one of the main causes of the worldwide current biodiversity crisis (Blackburn et al 2019;Liu et al 2020;Pyšek et al 2020). Following a parsimony principle, all alien species may exert impacts on native ecosystems (Kumschick and Nentwig 2010;Blackburn et al 2014;Evans et al 2018), and these effects should be limited through addressed management actions (Hulme 2006;Mazzamuto et al 2020;Saavedra and Medina 2020), often involving high economic costs (Bacher et al 2018;Diagne et al 2020). Early detection and surveillance programs of new invasions (or newly invaded areas) by alien 1 3 in Mediterranean countries (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we stress that social considerations should not prevent relevant governmental bodies from pursuing efforts to control the species. Recently, a management plan in the Canary Islands (Spain) successfully eradicated a small number of rose-ringed parakeet from La Palma island by combining trapping and shooting with social collaboration (Saavedra and Medina, 2020). We recommend, therefore, a multidisciplinary approach, combining various methods to remove the parakeets, and building as much social learning and trust as possible by promoting effective communication and education of the public (Crowley et al, 2019;Perry and Perry, 2008;Shackleton et al, 2019).…”
Section: Implications For Managementmentioning
confidence: 99%